Density, viscosity and CO2 solubility of novel solvent - Kee, W.M. (Trans Tech Publications Ltd, 2014)
Carbon dioxide (CO2) is the major cause of accelerating global warming. It is importantto employ efficient method to capture CO2. Absorption is the most established technique to separate CO2 and amines are most commonly used as solvent. In this study, density and viscosity of an amine based novel solvent named Stonvent were investigated at temperature ranging from 298.15 K to 338.15 K. CO2 solubility in Stonvent was measured at varying pressures, temperatures and concentrations. The experiments were conducted at temperatures (303.15, 318.15 and 333.15) K, and at pressures (0.5, 1, 1.5 and 3) MPa over a wide range of concentration (10, 20, 30 and 100) mass . Solubility of CO2 was determined from pressure drop due to absorption of CO2 into solvent within equilibrium cell. Absorption capacity of Stonvent increases significantly with increasing pressure. Solubility of CO2 in Stonvent is higher compared to Monoethanolamine (MEA), 1-amino-2-propanol (MIPA) and 2-amino-2-methyl-1,3-propanediol (AMPD) at elevated pressure, hence posing Stonvent as an attractive alternative for acid gas absorption in high pressure conditions. Substantial increase in CO2 loading was observed when concentration of Stonvent is increased and when temperature is decreased. Â© (2014) Trans Tech Publications, Switzerland.